Regulating Precariousness? The Temporary Employment Relationship Under the NAFTA and the EC Treaty - Vosko, Leah F. (Relations industrielles / Industrial Relations, 1998)
Regulatory responses to the spread of non-standard forms of employment in North America and Europe are examined, particularly those measures directed at the temporary employment relationship associated with the temporary help services industry. Through an analysis of international labor conventions, country-specific regulations and supranational initiatives, it is demonstrated that countries party to the NAFTA and the European Community both endorse strategies aimed at numerical flexibility yet they take divergent regulatory approaches in response to the growth of temporary employment. While North American countries opt for non-regulation, the European Community is attempting to establish basic protections for workers engaged in temporary employment.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment practices; International; Labor Unions; Labor law; Labor standards; Regulation; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Temporary employment; Trade agreements